Woman's cause : what the work of the Rev. Mary Baker Eddy, discoverer and founder of Christian Science has done for it / by Carol Norton. - Norton, Carol, 1869-1904. (Tufts University. Tisch Library., 2016)
First edition.; 1 online resource (32 pages); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.